Brief references about teacher training in Portugal: The importance of school associations training centers – CFAE and the collaborative experience between Brazil and Portugal in continuous training through the digital teaching on network course - Lira, L. A. R.; Moreira, J. A.; Serra, I. M. R.; Henriques, S. (International Journal of Human Sciences Research, 2022)
This article, is a clipping that derives from a post-doctoral research report carried out at the Open University of Portugal in the field of teacher training, it was sought, through a bibliographic and documentary research, approaches and historical evidence, from authors who discuss the theme in an evolutionary process, and also, in the legal basis in the educational context in Portugal. In this sense, it was possible to know the organizational aspects of the basic academic structure of teaching in Portugal with regard to continuous training and specialized training of teachers, whose paths are directed to the possibilities of improvement and professional development throughout the life of these teachers in their careers. It was also considered to analyze the rise and importance attributed to the Training Centers for School Associations - CFAEs, which act as decentralized networks integrating schools, teachers and managers through training plans organized territorially. At the end of the study, we carried out a brief analysis of the Course entitled, Digital Teaching in Network, idealized by the Open University of Portugal, having been applied to Brazilian and Portuguese professors in a collaborative regime through the Coordination for the Improvement of Higher Education Personnel (CAPES), the State University of Maranhão (UEMA) and the Open University of Portugal (UAb-PT)